Effects of Peers on Child Pedestrian Behaviors in a Virtual Traffic Context. (5th January 2019) - Morrongiello, Barbara A; Corbett, Michael; Koutsoulianos, Stephanie; Foster, Avianna
Abstract: Objectives: Research shows that school-aged children are at high risk of pedestrian injury when they cross streets with peers. How peers exert their influence is unknown. Using a fully immersive virtual reality pedestrian environment, this study examined the impact of peers on children's pedestrian behaviors. Methods: 137 children were assigned either to a control, peer observer, or peer-safety or peer-risky modeling condition. Street-crossing behaviors were measured twice (baseline, postbaseline), with group comparisons (control vs. test condition) of postbaseline scores conducted. Results: Children who observed a peer modeling risky behaviors imitated this. No significant influences were found in the peer observation or safe modeling conditions. Conclusions: Peers may elevate other children's risk of pedestrian injury through modeling risky crossings. Implications for prevention are discussed.